PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA BAGI ANAK TUNAGRAHITA RINGAN KELAS III DI SLB SABILUNA PARIAMAN - Desni Humaira; Fatmawati Fatmawati; Zulmiyetri Zulmiyetri (Universitas Negeri Padang, 2012)
This research is motivated by the problems that researchers found in a field that in class III C SLB Sabiluna Pariaman. The researchers looked at in the process of Indonesian learning the teacher to experience difficulty in presenting matter to students mental retardation because student situation that different in one class. Based on these then the problems that are examined in research is: (1) How is the implementation of the Indonesian learning for students mental retardation in SLB Sabiluna Pariaman? (2) What are the obstacles encountered, (3) How do teacher for overcome the obstacles. The method used is the qualitative descriptive. The research subject is teacher class and mental retardation class III.